Analisis Terhadap Dalil Hukum dalam Fatwa Dewan Syariah Nasional Majelis Ulama Indonesia Nomor 6 Tahun 2000 Tentang Istishna - Noorwahidah Haisyi (Islamic Economics and Business Faculty of UIN Antasari, 2019)
The legal basis stated in the Fatwa of the National Sharia Council (DSN) Number 6 of 2000 concerning Istishna' is very minimal, because it only consists of two hadith, one fiqh rule, and one ijtihad. This research was carried out to assess the accuracy of these four legal bases against the istishna’ provisions contained in the fatwa, and to trace other legal bases of the Qur'an and hadith which were deemed more relevant. This is a qualitative research with the library research approach. The legal material studied is the fatwa of DSN No. 6 of 2000 concerning Istishna', as well as legal arguments in the form of the Qur'an and hadith. The findings are then analyzed descriptively. The results of the research show that the legal basis used by the DSN to support istishna’ provisions in this fatwa is indeed quite accurate, but there are at least two verses of the Qur'an and two hadiths that are more relevant as the basis of these istishna’ legalities.